Preparation method of antibacterial foam dressing
By introducing negatively charged molybdenum disulfide nanosheets into antibacterial foam dressings and using photothermal conversion technology, the problem of existing antibacterial foam dressings’ limited effect on drug-resistant bacteria is solved, achieving high efficiency, low toxicity, broad-spectrum antibacterial effects, and Simplified process flow.
Patent Information
- Application Number
- CN202411151352.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2025-01-24
AI Technical Summary
Existing antibacterial foam dressings have limited effects when facing drug-resistant bacteria, and conventional methods have toxicity risks and process complexity problems.
Negatively charged molybdenum disulfide nanosheets were synthesized through a hydrothermal method, and N-methyldiethanolamine was used as a dispersant, supplemented by ultrasound to evenly disperse the nanosheets in polyurethane prepolymer, and then foamed to synthesize an antibacterial foam dressing. The dressing can achieve photothermal conversion under appropriate lighting and achieve antibacterial effects.
The effect of high -efficiency and low toxicity, broad -spectrum antibacterial effects, avoiding the emergence of drug resistance, simplifying the process process, ensuring the safety and practicality of the dressing.
Smart Images

Figure CN119345429A_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of medical dressing manufacturing, in particular to a method for preparing an antibacterial foam dressing which has simple process, physical antibacterial properties, is not prone to drug resistance and has a broad-spectrum antibacterial effect. Background technology:
[0002] With the gradual development of the field of wound care, products for wound exudate management are emerging in an endless stream. For wound exudate, it is necessary to ensure the absorption of exudate and maintain a suitable environment to ensure healing. Excessive wound exudate may also increase the risk of wound infection. Therefore, there is a prominent demand for dressings with exudate management and antibacterial effects. Compared with traditional dressings, it has the function of preventing and controlling wound infection, which brings great convenience to medical staff and patients. At present, there are two schemes for preparing antibacterial foam dressings on the market: one is to mix soluble metal solutions, metal complexes, nano-scale metal inclusion materials, etc. with dressing matrix, and the metal ion components may enter the body with the wound, which has a certain toxicity risk. For example, CN111001029B discloses a method for preparing antibacterial foam dressings, by dispersing antibacterial metal powder in water-based polyurethane prepolymer, mixing and foaming with water to obtain polyurethane foam dressings with antibacterial function; the other is to add natural antibacterial components (such as antibiotics, disinfectants, etc.) to the dressing matrix, such as CN110025817A discloses an antibacterial fiber prepared by a composite of corn protein / plant essential oil, mixing the antibacterial components extracted from plants into the spinning solution, and preparing the composite fiber antibacterial dressing by electrospinning. However, with the gradual development of drug-resistant bacteria, the effect of this scheme on drug-resistant bacteria is becoming increasingly limited. Therefore, the limitations of common antibacterial methods are increasing, and new antibacterial solutions are more urgent. Physical sterilization methods have attracted extensive research. Among them, photothermal therapy is a non-invasive treatment method that converts light energy into heat energy by irradiating photothermal materials with external light sources to kill bacteria. It is highly efficient and low-toxic, and is very suitable for the application and promotion of dressings. Summary of the invention:
[0003] In view of the shortcomings and deficiencies in the prior art, the present invention proposes a method for preparing an antibacterial foam dressing which is highly efficient, low toxic, simple in process, not prone to drug resistance and has a broad-spectrum antibacterial effect.
[0004] In order to solve the problem that nanomaterials are difficult to disperse and easy to agglomerate, molybdenum disulfide nanosheets are synthesized by hydrothermal method with negative charge on the surface. N-methyldiethanolamine is used as a dispersant, and ultrasound is used to disperse the molybdenum disulfide nanosheets in the prepolymer. As the viscosity gradually increases during the reaction, the agglomeration phenomenon of the molybdenum disulfide nanosheets is significantly improved. The molybdenum disulfide nanosheets synthesized by foaming are evenly dispersed in the foam dressing matrix. Under light of appropriate wavelength (600-800nm), photothermal conversion can be achieved to achieve an antibacterial effect.
[0005] The present invention is achieved by the following measures:
[0006] A method for preparing an antibacterial foam dressing, characterized in that molybdenum disulfide nanosheets are loaded on the foam dressing, specifically comprising the following steps:
[0007] Step 1: preparing molybdenum disulfide nanosheets;
[0008] Step 2: Ultrasonic dispersion of molybdenum disulfide nanosheets and N-methyldiethanolamine, wherein the mass ratio of N-methyldiethanolamine to molybdenum disulfide is 1:1, and then prepolymer is added to prepare component A, wherein the ratio of prepolymer to molybdenum disulfide nanosheets is: isocyanate 35.5±
[0009] 10wt%, polyether polyol 60.5±10wt%, dispersed molybdenum disulfide 4.0±2wt%;
[0010] Step 3: Synthesizing component B: Mix the crosslinking agent, the pore opening agent, the surfactant, and deionized water in the following ratios: 7.5±3wt% of the crosslinking agent, 15.0±5wt% of the pore opening agent, 15.0±5wt% of the surfactant, and 62.5±10wt% of the deionized water, and stir evenly to obtain component B;
[0011] Step 4: Synthesize the antibacterial foam dressing: Mix the component A obtained in step 2 and the component B obtained in step 3 at a mass ratio of 1:0.5-2.0, stir and foam at high speed, cast and form, and then dry to obtain the antibacterial foam dressing.
[0012] Step 1 of the present invention is specifically as follows: 2.06g of anhydrous sodium molybdate and 4.12g of thioacetamide are weighed by using an analytical balance, and the two are dissolved in 450ml of deionized water, stirred for 30min to form a uniform solution, and the solution is transferred to a polytetrafluoroethylene liner of a hydrothermal reactor, and the reactor is placed at 220°C for reaction for 24h, and after the reaction is completed, the reaction solution is cooled to room temperature, and the reaction solution is centrifuged at high speed, and the centrifugation parameter is 9000rpm, 10min, and then anhydrous ethanol and deionized water are added respectively for repeated washing, and each washing is repeated three times, and the speed and time during centrifugation are kept consistent, and the bottom precipitate is collected, and placed in a -18°C refrigerator for freezing for 8h, and finally the sample is placed in a freeze dryer for vacuum drying for 24h to obtain molybdenum disulfide nanosheets.
[0013] Step 2 of the present invention is specifically as follows: adding polyether polyol to a three-necked flask, heating an oil bath pot to maintain a temperature of 60° C. and a rotation speed of 100 rpm, adding isocyanate after the temperature is stable, and the viscosity gradually increases. 1 hour after the addition of isocyanate, adding molybdenum disulfide nanosheets dispersed by N-methyldiethanolamine, as described in step 2, the dispersion means is a mixture of the two assisted by ultrasound, N-methyldiethanolamine is an oily liquid, and the molybdenum disulfide nanosheets are solid powders, and there is an electrostatic effect between the two. To ensure the effect, ultrasound is used to assist and ensure uniform dispersion, the viscosity of the reaction system begins to increase, the rotation speed is maintained and ultrasound is used, the ultrasonic power is 150 W, the frequency is 40 kHz, and then The reaction was continued for 1 hour, and the reaction was continued for 2 hours after the ultrasound was turned off to obtain component A. The viscosity of component A was controlled to ensure the dispersion effect of molybdenum disulfide nanosheets. The viscosity of component A should be above 15000 mPa at 25° C., wherein the isocyanate and the polyether undergo a chemical reaction, and the molecular weight increases. As the reaction time increases, the viscosity gradually increases, and the viscosity of the prepolymer can reach a maximum of 23000 mPa·S at 25° C., wherein the polyether polyol described in component A is one or more of polyether 330 and polyether 360; the isocyanate is one or more of toluene diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate and isophorone diisocyanate.
[0014] Step 3 of the present invention is specifically as follows: weighed cross-linking agent, pore opening agent, surfactant and deionized water are added into a beaker successively, stirred evenly with a stirrer, the rotation speed is controlled to be 100 rpm, and stirred for more than 4 hours to obtain component B, wherein the cross-linking agent described in component B is one or more of glycerol, diglycerol and triglycerol; the pore opening agent is one or more of K2800 and k757; and the surfactant is one or more of poloxamer 407, poloxamer 188, Tween-20, Tween-40, Tween-60 and Tween-80.
[0015] In step 4 of the present invention, the synthesized component A and component B are mixed in a mass ratio, stirred and foamed under a stirrer with a rotation speed of 3000 rpm, and a release paper is laid under the stirrer for cast molding. The speed is controlled at 3-5 m / min, and the thickness of the foam dressing is controlled by adjusting the pressure roller. Specifically, the thickness is controlled within 10 mm, and the antibacterial foam dressing coil is obtained by drying in an oven at 60° C. for 5 min.
[0016] Compared with the prior art, the present invention introduces molybdenum disulfide nanosheets into polyurethane foam dressings to prepare composite dressings, improves the agglomeration of nanosheets through the viscosity and electrostatic effect of component A, introduces molybdenum disulfide nanosheets for photothermal antibacterial without affecting the water absorption and pore structure of the foam dressing, and it has been verified that the antibacterial effect can be achieved under visible light (660nm), avoiding the risks brought by conventional means. Description of the drawings:
[0017] Attached Figure 1 4 is a curve diagram of the temperature difference on the upper surface of the foam dressing in an embodiment of the present invention.
[0018] Attached Figure 2 is a temperature difference curve diagram of the lower surface of the foam dressing in an embodiment of the present invention. Specific implementation method:
[0019] The present invention will be further described below in conjunction with the embodiments.
[0020] Example 1
[0021] This example provides a method for preparing an antibacterial foam dressing, and the proportions of each component are shown in the following table:
[0022]
[0023] Component A and component B were synthesized according to the proportions described in the table, wherein the synthesis steps of component A were as follows: polyether 360 was added to a three-necked flask, and the oil bath was heated to maintain the temperature at 60°C and the rotation speed at 100 rpm. After the temperature was stable, toluene diisocyanate was added, and the viscosity gradually increased. One hour after the addition of toluene diisocyanate, molybdenum disulfide nanosheets dispersed by N-methyldiethanolamine were added, and the viscosity of the reaction system began to increase. The rotation speed was maintained and ultrasound was used with an ultrasound power of 150 W and a frequency of 40 kHz. The reaction was continued for 1 hour, and the reaction was continued for 2 hours after the ultrasound was turned off to obtain component A.
[0024] The synthesis steps of component B are as follows: weighed glycerol, K2800, poloxamer 407 and deionized water are added into a beaker in turn, stirred evenly with a stirrer, the rotation speed is controlled at 100 rpm, and stirred for more than 4 hours to obtain component B; the two are quickly mixed for 10 seconds at room temperature by a stirring paddle at 3000 rpm, and then cast on release paper (speed is 4 m / min), the foaming thickness is controlled at 5 mm, and dried in an oven at 60°C for 5 minutes.
[0025] Example 2
[0026] This example provides a method for preparing an antibacterial foam dressing, and the proportions of each component are as shown in the following table:
[0027]
[0028] The components A and B were synthesized according to the proportions described in the table. The synthesis steps of component A are as follows: polyether 360 was added to a three-necked flask, and the oil bath was heated to maintain the temperature at 60°C and the speed at 100 rpm. After the temperature stabilized, toluene diisocyanate was added, and the viscosity gradually increased. One hour after the addition of toluene diisocyanate, molybdenum disulfide nanosheets dispersed by N-methyldiethanolamine were added, and the viscosity of the reaction system began to increase. The speed was maintained and assisted by ultrasound, with an ultrasonic power of 150 W and a frequency of 40 kHz, and the reaction continued for 1 hour. After the ultrasound was turned off, the reaction continued for 2 hours to obtain component A.
[0029] The synthesis steps of component B are as follows: weighed glycerol, K2800, poloxamer 407 and deionized water are added into a beaker successively, stirred evenly with a stirrer, the speed is controlled at 100 rpm, and stirred for more than 4 hours to obtain component B;
[0030] Thereafter, the two were rapidly mixed at room temperature by a stirring paddle at 3000 rpm for 10 seconds, and then cast on release paper (speed of 4 m / min), the foaming thickness was controlled at 5 mm, and dried in an oven at 60° C. for 5 minutes.
[0031] Embodiment 3:
[0032] This example provides a method for preparing an antibacterial foam dressing, and the proportions of each component are as shown in the following table:
[0033]
[0034] The components A and B were synthesized according to the proportions described in the table: wherein the synthesis steps of the component A were as follows: polyether 360 was added to a three-necked flask, and the oil bath was heated to maintain the temperature at 60°C and the rotation speed at 100 rpm. After the temperature stabilized, toluene diisocyanate was added, and the viscosity gradually increased. One hour after the addition of toluene diisocyanate, molybdenum disulfide nanosheets dispersed by N-methyldiethanolamine were added, and the viscosity of the reaction system began to increase. The rotation speed was maintained and ultrasound was used with an ultrasound power of 150 W and a frequency of 40 kHz. The reaction was continued for 1 hour, and the ultrasound was turned off and the reaction was continued for 2 hours to obtain the component A.
[0035] The synthesis steps of component B are as follows: weighed glycerol, K2800, poloxamer 407 and deionized water are added into a beaker successively, stirred evenly with a stirrer, the speed is controlled at 100 rpm, and stirred for more than 4 hours to obtain component B;
[0036] The two were rapidly mixed at room temperature by a stirring paddle at 3000 rpm for 10 seconds, and then cast on release paper (speed of 4 m / min), the foaming thickness was controlled at 5 mm, and dried in an oven at 60° C. for 5 minutes.
[0037] Comparative Example 1
[0038] The following is a comparative sample. During its preparation, the proportions of each group are as follows:
[0039]
[0040] The A and B components were synthesized according to the proportions described in the table:
[0041] The synthesis steps of component A are as follows: add polyether 360 into a three-necked flask, heat the oil bath to maintain the temperature at 60°C and the speed at 100 rpm, add toluene diisocyanate after the temperature stabilizes, and continue the reaction for 3 hours to obtain component A;
[0042] The synthesis steps of component B are as follows: weighed glycerol, K2800, poloxamer 407 and deionized water are added to a beaker in sequence, stirred evenly with a stirrer, the speed is controlled at 100 rpm, and stirred for more than 4 hours to obtain component B. The two are quickly mixed for 10 seconds at room temperature by a stirring paddle at 3000 rpm, and then cast on release paper (speed is 4 m / min), the foaming thickness is controlled at 5 mm, and dried in an oven at 60°C for 5 minutes.
[0043] Comparative Example 2:
[0044] The following are comparative foam dressing samples, and the distribution ratios of each group are shown in the following table:
[0045]
[0046] It can be seen that the sample in this example also contains molybdenum disulfide nanomaterials, but the molybdenum disulfide nanosheets that have not been dispersed are used. The components A and B are synthesized according to the proportions described in the table. The synthesis steps of component A are as follows: polyether 360 is added to a three-necked flask, and the oil bath is heated to maintain the temperature at 60°C and the speed at 100rpm. After the temperature stabilizes, toluene diisocyanate is added, and the viscosity gradually increases. One hour after the addition of toluene diisocyanate, N-methyldiethanolamine and molybdenum disulfide nanosheets are added successively, and the viscosity of the reaction system begins to increase. The speed is maintained and assisted by ultrasound, the ultrasonic power is 150W, the frequency is 40kHz, and the reaction is continued for 1 hour. After the ultrasound is turned off, the reaction is continued for 2 hours to obtain component A.
[0047] The synthesis steps of component B are as follows: weighed glycerol, K2800, poloxamer 407 and deionized water are added into a beaker successively, stirred evenly with a stirrer, the speed is controlled at 100 rpm, and stirred for more than 4 hours to obtain component B;
[0048] The two were rapidly mixed at room temperature by a stirring paddle at 3000 rpm for 10 seconds, and then cast on release paper (speed of 4 m / min), the foaming thickness was controlled at 5 mm, and dried in an oven at 60° C. for 5 minutes.
[0049] The following is a comparative analysis of the photothermal properties of the dressing samples obtained in the examples and comparative examples:
[0050] Place an antibacterial polyurethane foam dressing with a size of 5cm×5cm and a thickness of 5mm horizontally in a surface dish, add PBS buffer to absorb liquid and swell to simulate the use of foam dressings, and then evenly irradiate the sample under visible light conditions with a light intensity of not less than 300Lux. Use an infrared temperature gun to read the surface temperature of the same part every 1min. Test the upper and lower surfaces of the foam dressing for 20min and draw temperature rise curves for different samples. To reduce contingency, repeat each sample three times and take the average value. The surface temperature difference of the foam dressing is as shown in the attached figure. Figure 1 As shown in the figure, the temperature difference on the lower surface of the foam dressing is as shown in the figure. Figure 2 As shown;
[0051] The swelling rate test of the foam dressing samples obtained in the examples and comparative examples is as follows:
[0052] Cut a 5cm*5cm antibacterial foam dressing, weigh the mass m0, immerse the antibacterial foam dressing in a beaker containing test liquid A for 5 minutes until the liquid is absorbed saturated, remove the excess liquid, remove the excess liquid with filter paper, and then weigh m1. The swelling rate is calculated by the following formula:
[0053]
[0054]
[0055] Porosity test:
[0056] The porosity test was performed by the ethanol replacement method. A 5cm*5cm antibacterial foam dressing was taken, its mass W1 was accurately weighed, and it was immersed in anhydrous ethanol until saturated. After draining the ethanol, the mass W2 of the antibacterial foam after saturated absorption was accurately weighed. The porosity was calculated by the following formula:
[0057]
[0058] Where ρ is the density of ethanol and V is the volume of the foam dressing before immersion in ethanol.
[0059]
[0060] Antibacterial effect analysis:
[0061] The uniform mixing of the molybdenum disulfide nanosheets was confirmed by Example 2 and Comparative Example 2. In Comparative Example 2, an equal amount of molybdenum disulfide nanosheets was added during the synthesis of component A, and the antibacterial performance comparison proved that the antibacterial effect of the molybdenum disulfide nanosheets dispersed by electrostatic action during the synthesis of component A was better.
[0062] Cytotoxicity and antibacterial properties
[0063]
[0064] Note: Among the test items in the table, cytotoxicity is tested in accordance with GB / T 16886.5-2017 Biological Evaluation of Medical Devices Part 5: In Vitro Cytotoxicity Test; antibacterial rate is tested in accordance with WS / T 650-2019 Evaluation Method for Antibacterial and Antibacterial Effects.
[0065] The present invention adopts a physical method to achieve the antibacterial effect, and loads the molybdenum disulfide nanosheets through electrostatic action, which will not affect the chemical reaction in the foaming process of the polyurethane foam dressing. At the thickness described in the present invention, the temperature is raised by 20°C under visible light, and the antibacterial foam dressing is successfully prepared. In addition, the polyurethane foam dressing has a special porous structure. The antibacterial foam dressing still has good porosity after the introduction of the nanosheets, and does not affect the liquid absorption performance of the foam. By testing the cytotoxicity and antibacterial rate, it is confirmed that the polyurethane foam dressing has an antibacterial effect while not producing cytotoxicity, which provides a new idea for clinical application.
Claims
1. A method for preparing an antibacterial foam dressing, characterized in that: The foam dressing is loaded with molybdenum disulfide nanosheets, which specifically includes the following steps: Step 1: preparing molybdenum disulfide nanosheets; Step 2: fully mixing molybdenum disulfide nanosheets and prepolymer to prepare component A, wherein the ratio of the prepolymer to the molybdenum disulfide nanosheets is: 35.5±10wt% of isocyanate, 60.5±10wt% of polyether polyol, and 4.0±2wt% of molybdenum disulfide; Step 3: synthesizing component B, mixing a crosslinking agent, a pore opening agent, a surfactant, and deionized water in a ratio of: 7.5±3wt% of crosslinking agent, 15.0±5wt% of pore opening agent, 15.0±5wt% of surfactant, and 62.5±10wt% of deionized water, and stirring evenly to obtain component B; Step 4: Synthesize the antibacterial foam dressing: Mix the component A obtained in step 2 and the component B obtained in step 3 at a mass ratio of 1:0.5-2.0, stir to foam, cast into a film, and dry to obtain the antibacterial foam dressing.
2. The method for preparing an antibacterial foam dressing according to claim 1, characterized in that: Step 1 is specifically as follows: 2.06 g of anhydrous sodium molybdate and 4.12 g of thioacetamide are weighed using an analytical balance, and the two are dissolved in 450 ml of deionized water, stirred for 30 min to form a uniform solution, and the solution is transferred to the polytetrafluoroethylene liner of a hydrothermal reactor. The reactor is placed at 220° C. for reaction for 24 h. After the reaction is completed, it is cooled to room temperature, and the reaction solution is centrifuged at 9000 rpm for 10 min. Then, anhydrous ethanol and deionized water are added and washed three times each. The speed and time during centrifugation are kept consistent. The bottom precipitate is collected and placed in a -18° C. refrigerator for 8 h. Finally, the sample is placed in a freeze dryer for vacuum drying for 24 h to obtain molybdenum disulfide nanosheets.
3. The method for preparing an antibacterial foam dressing according to claim 1, characterized in that: Step 2 is specifically as follows: the molybdenum disulfide nanosheets prepared in step 1 are placed in N-methyldiethanolamine at a mass ratio of 1:1, and ultrasonically dispersed for later use. The polyether polyol is added to a three-necked flask, and the oil bath is heated to maintain a temperature of 60°C and a speed of 100rpm. After the temperature stabilizes, isocyanate is added. One hour after the addition of isocyanate, the dispersed molybdenum disulfide nanosheets are added. The viscosity of the reaction system begins to increase. The speed is maintained and ultrasound is used with an ultrasonic power of 150W and a frequency of 40kHz. The reaction continues for 1 hour. After the ultrasound is turned off, the reaction continues for 2 hours to obtain component A. The viscosity of component A is controlled to ensure the dispersion effect of the molybdenum disulfide nanosheets. The viscosity of component A should be above 15000mPa at 25°C.
4. The method for preparing an antibacterial foam dressing according to claim 1, characterized in that: Step 3 is specifically as follows: the weighed cross-linking agent, pore opening agent, surfactant and deionized water are added into a beaker in turn, stirred evenly with a stirrer, the rotation speed is controlled to be 100 rpm, and stirred for more than 4 hours to obtain component B, wherein the cross-linking agent described in component B is one or more of glycerol, diglycerol, and triglycerol; the pore opening agent is one or more of K2800 and k757; and the surfactant is one or more of poloxamer 407, poloxamer 188, Tween-20, Tween-40, Tween-60, and Tween-80.
5. The method for preparing an antibacterial foam dressing according to claim 1, characterized in that: In step 4, the synthesized component A and component B are mixed in a mass ratio, stirred and foamed under a stirrer with a rotation speed of 3000 rpm, release paper is laid under the stirrer, and cast into a film. The speed is controlled at 3-5 m / min, and the thickness of the foam dressing is controlled by adjusting the pressure roller. The thickness is controlled within 10 mm, and the film is dried in an oven at 60°C for 5 min to obtain an antibacterial foam dressing coil.
Citation Information
Patent Citations
Preparation and application of corn protein / plant essential oil composite antibacterial fiber dressing
CN110025817A
An antibacterial foam dressing and its preparation method
CN111001029B